Strategic Human Resource Management in the Context of Taxation: A Systematic Literature Mapping - Hasanuddin Djumakking; Rahmi Rahmi (Journal Social Society, 2025)
The transformation of the global tax system due to digitalization, globalization and policy reform demands a strategic reorientation in human resource (HR) management in the tax sector. Strategic Human Resource Management (SHRM), which aligns workforce capabilities with institutional goals, has been proven effective in various sectors, but its application in tax policy and administration is still minimally explored. This study uses a Systematic Literature Mapping (SLM) approach to 45 scientific articles published 2014–2024 from the Scopus, Web of Science, and EBSCOhost databases. Thematic analysis identified five main clusters: strategic competency development, tax ethics and morals, SHRM in digital tax, HR policy alignment, and institutional comparative studies. The results of the study show that although SHRM is recognized as increasingly important for the performance of tax authorities, research in this area remains scattered, dominated by qualitative approaches in OECD countries, and lacks a theoretical foundation. New themes such as SHRM's role in driving ethical compliance and digital transformation need to be further researched. This study calls for research that is theoretically, methodologically sound, and contextually diverse, and provides practical recommendations for strengthening SHRM in fiscal governance and workforce modernization.